Chronology of drug treatment of migraine attack - Silva Néto, Raimundo Pereira da (Headache Medicine, 2011)
In the past, migraine was treated only during attacks with the knowledge and culture of each civilization. In the meantime, the use of medicinal herbs has contributed to the emergence of the first analgesic drugs, despite their non-specificity for headaches, such as acetylsalicylic acid and dipyrone. During the twentieth century, other nonsteroidal anti-inflammatory drugs and the first specific drugs for migraine were synthesized: ergotamine and triptans. The development of triptans is considered the greatest advance in the treatment of migraine attacks in the past 50 years.